Land of Fire - Ryan, Chris, 1961- (London Century, 2002)
During the Falklands War, young SAS trooper Mike Hood risked his life to capture an Argentinian girl spy. Twenty years on, an Argentine military junta is returned to reinvade the Falkland Islands. Mike is soon faced with a conflict of loyalties.
Keywords: Great Britain. Army. Special Air Service -- Falkland Islands War (1982) -- Women spies